2021
DOI: 10.1002/pan3.10185
|View full text |Cite
|
Sign up to set email alerts
|

From dirty to delicacy? Changing exploitation in China threatens the world's largest amphibians

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…On the bright side, social science methods such as questionnaire‐based surveys are increasingly used to gather local and traditional ecological knowledge (e.g. species' status and trends; past and present human–environmental interactions and extinction drivers) to inform conservation planning for poorly known and highly threatened species, although these approaches are not yet applied consistently or across all relevant contexts (Lin et al, 2019; Nash et al, 2016; Pan et al, 2016; Turvey et al, 2010, 2017, 2021). Such methods can also help collect data on the perceptions, attitudes and characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the bright side, social science methods such as questionnaire‐based surveys are increasingly used to gather local and traditional ecological knowledge (e.g. species' status and trends; past and present human–environmental interactions and extinction drivers) to inform conservation planning for poorly known and highly threatened species, although these approaches are not yet applied consistently or across all relevant contexts (Lin et al, 2019; Nash et al, 2016; Pan et al, 2016; Turvey et al, 2010, 2017, 2021). Such methods can also help collect data on the perceptions, attitudes and characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese giant salamanders Andrias spp., the world's largest amphibians, formerly occurred across much of central and southern China (Chen et al, 2018). Historical taboos against eating them were widespread in rural communities, although they were also sometimes hunted for local consumption, particularly by ethnic minority groups including the Tujia and Yao (Cunningham et al, 2016; Turvey et al, 2021). However, the development of a large‐scale national giant salamander farming industry since the 2000s has led to commercial demand for wild breeding stock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen years ago, Stuart et al (2008) edited their compendium "Threatened World of Amphibians" as a result of the Global Amphibian Assessment and synthesized knowledge on the science and threats detrimentally impacting amphibian species on a global scale. Threats such as habitat destruction (Cox et al 2006), pollution (Blaustein and Johnson 2003), domestic use and trade (Mohneke 2011;Turvey et al 2021), international trade (Andreone et al 2006;Carpenter et al 2014;Auliya et al 2016), and climate change (Blaustein et al 2010) have been well studied in many areas, but amphibians are also particularly vulnerable to pathogens, such as ranaviruses (Cunningham et al 1996;Daszak et al 1999;Miller et al 2011;Bayley et al 2013), mycotic diseases (Daszak et al 1999;Fitzpatrick et al 2018), and parasites (Kim et al 2016). A recent study also revealed that frogs act as intermediate hosts of the parasite Alaria alata, and human consumption of frogs' legs containing larvae of the parasite can promote alariosis, a potentially deadly parasitic infection (Korpysa-Dzirba et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Populations of A. davidianus have declined remarkably within the past 50 years due to habitat loss, environmental change and pollution, overharvesting, infection diseases, and exploitation for food. As a result, A. davidianus has been included in the national class II protected species in China and in the list of Appendix I of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES, 2008) (2)(3)(4)(5). In parallel to this rapid decline of wild populations, farming of A. davidianus has developed rapidly since 2005.…”
Section: Introductionmentioning
confidence: 99%